Implementing exercise recommendations into clinical practice—new findings from mental health professionals' and patients' perspectives in a university psychiatric setting - Hirschbeck, Anna; Kossmann, David; Schwegler, Hannah; Greiner, Sophie-Kathrin; Hasan, Alkomiet; Roeh, Astrid (Frontiers in Sports and Active Living, 2024)
Introduction: To date, concrete recommendations for physical activity in psychiatric treatments are limited. Thus, we evaluated knowledge, barriers and beliefs associated with exercise prescription of mental health professionals (MHP) to people with mental illnesses. We aimed to identify patients’ barriers to exercise participation and to work out options addressing these barriers. Methods: In our cross-sectional and questionnaire-based investigation, we recruited medical, nursing and therapeutic staff and patients of a psychiatric clinic by email and personal contact. Questionnaires contained the German versions of The Exercise in Mental Illness Questionnaire (EMIQ-G) and the International Physical Activity Questionnaires (IPAQ). Results: We included 100 MHP and 100 patients. MHP had significantly more knowledge regarding positive effects of exercise on general health than patients. Exercise was prescribed mostly (48.4%) or always (37.9%) by MHP. The data showed missing education in exercise prescriptions and different recommendation behavior. Male patients seemed to experience exercise more often as a positive distraction and had lower physical health barriers than females. Discussion: Physical activity needs to be more integrated in psychiatric treatments. Some strategies as educating MHP and patients regarding potential benefits of exercise via psychoeducative brochures and adapting recommendations to individual symptoms could improve exercise behavior in psychiatric patients.